Promotion Strategy to Increase Sales of AL Fazza Residence Property at PT Wahana Persada Indonesia Makassar City - Mochtar Lutfi M; Hermawaty RK; Rawana Rawana (Universitas Negeri Makassar, 2022)
This study aims 1) to find out what promotional strategies are being carried out by PT. Wahana persada Indonesia in increasing sales of Al Fazza residence. 2) To find out the supporting factors and inhibiting factors in implementing promotional strategies in increasing sales of Al Fazza residence. This type of research was carried out using a qualitative descriptive approach. This research was carried out at PT. Wahana Persada Indonesia, which is located on Jalan Baling Tonjong, Manggala, Makassar City. when this research was conducted in January-February 2022. The data sources are primary data and secondary data. The focus of the research is promotion strategy. Data collection techniques are observation, interviews, and documentation. The results showed that 1). Promotion strategy of PT. Wahana Persada Indonesia in increasing sales by using the concept of a promotional mix (promotional mix). By using social media (instagram, whatsapp, and facebook), brochures, billboards and banners, sales promotions offer down payments that can be paid in installments and provide furniture promos, public relations are carried out by visiting institutions such as schools, campuses and offices , personal sales are also carried out by canvasing distributing brochures, following up, direct marketing is done by looking for relationships, catalogs and giving business cards. 2) supporting factors in implementing promotional strategies in increasing sales, namely marketing spirit, support system, continuous. The inhibiting factors are the Covid-19 pandemic, and the competition is quite tight.